?STRUCTURE, DEVELOPMENT AND REPRODUCTION OF A NEW SPECIES SCINAIA SAIFULLAHII (BONNEMAISONIALES, RHODOPHYTA) FROM THE NORTH ARABIAN SEA - HUSAIN, SYED AFAQ; SHAMEEL, MUSTAFA (Biological Sciences - PJSIR, 1997)
Scinaia saifullahii Afaq-Husain et ShameeJ, a new taxon of red algae belonging to the group of cylindrical and unconstricted species of Scinaia, from the coast of Pakistan has been described. Its vegetative, anatomical and reproductive structures were studiedcritically. These plants maybedistinguished fromother species ofScinaia by their large size (up to 25 em), generally large distance between successive furcations (up to 60 mm) and relatively large cystocarps (upto300urndiameter).Sizeandshapeofurticles, hypodermalcells,carposporangiaand carposporestogether distinguish it from allied species.